Right ventricle chamber of young trained athletes: morphology and function - Stefani, L.; de Luca, A.; Galanti, G. (Asian Journal of Sports Medicine, 2013)
Purpose: The study of the right ventricular (RV) chamber has been recently improved by use of the method 3D. In young asymptomatic trained athletes, RV is not routinely investigated if not in suspected disease. This study is designed to test if the method 3D compared to 2D, adds information to study of RV morphology and function, in the early stages of myocardial remodeling of a group of young athletes.